Ewing sarcoma. (5th April 2021) - Eaton, Bree R.; Claude, Line; Indelicato, Daniel J.; Vatner, Ralph; Yeh, Brian; Schwarz, Rudolf; Laack, Nadia
Abstract: Ewing sarcoma is a rare tumor that requires complex multidisciplinary management. This report describes the general management and standard radiotherapy guidelines in both North America (Children's Oncology Group) and Europe (International Society of Pediatric Oncology). Standard treatment involves multiagent induction chemotherapy followed by local treatment with surgery, definitive radiation, or a combination of surgery and radiation followed by additional chemotherapy and consolidation local treatment to metastatic sites. The data supporting the role of chemotherapy, surgery, and radiation and specific radiation therapy guidelines are presented.